Ex Post Evaluations of Exceptional Access Arrangements-Revised Guidance Note. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The Executive Board has agreed that post-program monitoring (PPM), with formal involvement of the Board, could be useful in certain cases. Specifically, the Board has decided that when a member's outstanding credit from the General Resources Account (GRA) of the Fund, or from the Fund as Trustee of the Poverty Reduction and Growth Trust (PRGT), or a combination thereof, exceeds a threshold of 200 percent of quota, and the member no longer has an arrangement or is not implementing a staff-monitored program with reports issued to the Board, there should be a presumption that the member will engage in PPM with the Fund of economic developments and policies after the expiration of the arrangement.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: EPE Report; EPE; EPES; PIN; PP